2007
DOI: 10.1111/j.1463-1318.2007.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Transanal endoscopic microsurgery: local recurrence rate following resection of rectal cancer

Abstract: Transanal endoscopic microsurgery is a safe procedure with obvious advantages over radical procedures. However, in this study the local recurrence rate is high. The recurrence rate may be an acceptable compromise in elderly or medically unfit patients but is hard to justify for curative intent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Transanal endoscopic microsurgery has already been shown to be effective treatment for selected benign or malignant rectal lesions [5–8]. In this series of 262 TEMS procedures, the mortality of 0.8% was within the range of 0–2% reported in the literature [4,7–9].…”
Section: Discussionmentioning
confidence: 70%
“…Transanal endoscopic microsurgery has already been shown to be effective treatment for selected benign or malignant rectal lesions [5–8]. In this series of 262 TEMS procedures, the mortality of 0.8% was within the range of 0–2% reported in the literature [4,7–9].…”
Section: Discussionmentioning
confidence: 70%
“…Of these 12 patients, 1 had recurrence, whereas 5 of the 24 patients who did not undergo salvage surgery had recurrence, yielding an overall recurrence rate of 16.7%. Other studies report higher recurrence rates after TEM for rectal cancer, such as Whitehouse et al, 26 who found a 26% recurrence rate in 23 patients with pT1 tumors, possibly owing to the small number of patients. A recent study published by Doornebosch et al 4 reported a local recurrence rate of 20.5% in 88 patients who underwent TEM for pT1 rectal cancer, with an overall survival of 31% at a 3-year follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…[66][67][68][69] on this basis, the previous asCRs parameter and guidelines from multiple societies included proctoscopy every 6 months. 9 however, the rate of identification of anastomotic recurrence at surveillance endoscopy has been only ~2%, 11,12 and no improvement in overall survival was demonstrated in earlier randomized studies.…”
Section: Surveillance Colonoscopy Is Recommended At 1 Year Af-mentioning
confidence: 99%